ANALISIS POLA KLASTER DAN ORIENTASI PASAR STUDI KASUS SENTRA INDUSTRI KERAJINAN LOGAM DESA TUMANG KECAMATAN CEPOGO KABUPATEN BOYOLALI - Rizka Choirunnisa; Bagio Mudakir (Diponegoro Journal of Economics, 2012)
ABSTRACT Cluster phenomenon has attracted the attention of economist to get involved in the location matters study that create a new paradigm. Tumang is tourism village industrial district of metal craft in Boyolali Regency has a characteristic and dominated by small-scale industry. The purpose of this study is to analyze cluster pattern and analyze factors which influence the market orientation in industrial district of metal craft Tumang ,Cepogo, Boyolali Regency used 60 respondents. This study uses Cluster Analysis to analyze cluster pattern refers to the variable in the Markussen model (1996) and Logistic Regression Model is used in this study to analyze the important factors that distinguish export-oriented industries and domestic-oriented industries. The results of the identification of the proposed cluster patterns Markusen, it can be concluded that the pattern of industrial district of metal craft Tumang Cepogo Boyolali Regency follows the pattern of clusters Marshallian and the Hub and Spoke. The results of binary logistic regression model analysis there are four variables that significantly influence the export market orientation of the labor, age of business, the buyer network, and the active promotion.